The role of the European U23 championships in the develeopment of elite athletes - Hanley, B. (New Studies in Athletics, 2014)
The European U23 Championships are an important competition showcasing young athletic talent. The expansion of competition in this age group provides a clear and contemporary rationale for studying these championships. Since its inception in 1997, this biennial competition has been used as a major milestone in the athlete's progress to world-class competition. In this study, athletes competing from 1999 to 2013 were observed. Their Global Wait (time taken between U23s and global championships) and Final Wait (transition time between U23s and reaching a final at global championships) along with successes were the criteria used for assessment. Interesting trends materialised regarding what events athletes continued to compete in or transitioned from (e.g. comparing throwers with combined events), and the time it took before competing at a global final (e.g. 800m women waited the longest). The measured success rate (finals and medal positions) of the U23 athletes within this study attests to the importance of these championships to athlete development.